2017
DOI: 10.1155/2017/5103145
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Tumor Lysis Syndrome in a Patient with a Dedifferentiated Endometrial Adenocarcinoma

Abstract: Tumor lysis syndrome (TLS) is an oncological emergency caused by massive cytolysis of malignant cells. This syndrome eventually induces metabolic abnormalities. TLS is observed mainly among tumors with rapid cell proliferation or high sensitivity to antineoplastic treatment. In rare cases, TLS occurs without any cytotoxic treatment. Previous reports have shown that alternative stress including proceeding infection or an operation might play a role in TLS. However, exact mechanism of spontaneous TLS remains unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Although spontaneous TLS is more common in hematological malignancies, it rarely develops in solid tumors. Small cell lung cancer, advance gastric cancer, endometrium cancer, hepatocellular carcinoma, colon carcinoma and over cancer from spontaneously TLS solid tumors have been described [7][8][9][10] .…”
Section: Resultsmentioning
confidence: 99%
“…Although spontaneous TLS is more common in hematological malignancies, it rarely develops in solid tumors. Small cell lung cancer, advance gastric cancer, endometrium cancer, hepatocellular carcinoma, colon carcinoma and over cancer from spontaneously TLS solid tumors have been described [7][8][9][10] .…”
Section: Resultsmentioning
confidence: 99%
“…Cairo-Bishop definition of laboratory tumor lysis syndromeIn our review of the literature, we found four reported cases of spontaneous TLS related to endometrial cancer.Harada et al, in 2015, reported the case of a 59-year-old female with multiple masses in the uterus and pathology positive for a dedifferentiated endometrial adenocarcinoma who met criteria for TLS without receiving cytotoxic therapy[4]. Two cases of spontaneous TLS were reported by Berger et al in 2017[5].…”
mentioning
confidence: 99%